Salafism, Digital Propaganda, and Hadith Representation in Memes: A Framing Analysis of Discourse on Instagram - Almughni Mika (Journal of Indonesian Digital Islamic Studies, 2026)
This article examines the representation of hadith in memes as part of Salafi digital propaganda practices on Instagram. Drawing on Robert N. Entman’s framing analysis, the study examines two Instagram accounts, @khalidbasalamahofficial and @thesunnah_path, that disseminate hadith-based memes on the prohibition of specifying particular times for grave visitation prior to Eid al-Fitr and Ramadan. The analysis demonstrates that the representation of hadith is constructed through a framing structure that defines local ritual practices as deviations, attributes their causes to inherited traditions, advances a moral evaluation that such practices are inconsistent with the Sunnah, and recommends a return to the prophetic model. The findings identify two configurations of digital religious authority: a hierarchical model grounded in explicit references to religious scholars and extended argumentation within post captions, and a populist-repetitive model that relies on the direct presentation of textual content in concise visual formats. These practices illustrate how Salafi digital propaganda operates through discursive framing that integrates a textual purification agenda with the affordances of social media environments. By integrating framing analysis with the theoretical frameworks of Digital Religion and Cyber Islamic Environments, this study argues that the representation of hadith in memes unfolds within a digital ecology that shapes the expression, legitimation, and articulation of religious authority in the cyber era.